ANALYSIS OF CAUSALITY RELATIONSHIP BETWEEN MIGRATION AND REAL WAGES IN THE US (Third Sector Social Economic Review, 2022)
The phenomenon of migration constitutes the common study area of social sciences from past to the present. Therefore, there are various reasons for migration. One of these reasons is coming from economic aspects. People who migrate for economic reasons generally immigrate to countries or regions that offer better living and income opportunities than where they live. The United States is one of the countries that hosts economic migration and has a large immigrant stock on its borders. Therefore, this study aims to examine the causal relationship between international migration and real wages in the USA between the years 1981 and 2017. The Augmented Dickey-Fuller and Phillips-Perron unit root tests were applied to the series in the first step of econometric analysis in the determination of the causality relationship. As a result of the applied unit root tests, it has been determined that the series are stationary at different levels. Then, the vector autoregressive model with increased delay was estimated and the Toda-Yamamoto causality test was applied to the series over this predicted model. As a result of the causality test, a bidirectional causality relationship was found between income and inflation. In addition, while there is a unidirectional causality relationship was found between inflation to real wages and unemployment; on the other hand, a unidirectional causality relationship was found between real wages to unemployment. Finally, no causal relationship was found between international migration and real wages, unemployment, income, and inflation.
Keywords: Migration; Real Wages; Income; Inflation; Unemployment; Causality